Relationship Between Diet Regulation, Parent Education, and Environmental Cleanliness on the Nutritional Status of Toddlers in Cibangkong Village, Pekuncen District, Banyumas Regency - Fitri Dian Kumala; Umi Solikhah (UM Purwokerto Press, 2022)
Background: The nutritional status of toddlers is a crucial thing that parents must know. It takes more parental attention to the growth and development of children at the age of toddlers, based on information that malnutrition in this golden age is irreversible. Objective: This study aims to determine the relationship between eating patterns, parental education and environmental hygiene with nutritional status figures in the area of Cibangkong Village, Pekuncen District, Banyumas Regency. Methods: The method used in this research is cross sectional with a sample of 78 respondents with simple random sampling. Results: Bivariate analysis with Chi-Square test found 3 significant factors related to dietary regulation on nutritional status as many as 56 respondents with a p-value of 0.037, education of parents as many as 32 respondents with a p-value of 0.026, and environmental hygiene as many as 65 respondents with p-value of 0.027. Conclusion: There was a significant correlation between 3 variables towards nutritional status of children under five years old in Cibangkong village, Pekuncen district, Banyumas regency.